’’Compulsory’’ Arrest of the Accused and the Impossibility of Arresting a Person on Directly Originated Reasonable Suspicion - Baghdasaryan, Gevorg (Bulletin of Yerevan University C: Jurisprudence, 2025)
The article is devoted to the practical issues of the protection of the right to personal liberty in the context of the legal regulations of arresting a person in case of the existence of reasonable suspicion that has arisen directly about having committed a crime and arrest for taking before the Court the accused who is at large. Referring to arresting a person in case of the existence of reasonable suspicion that has arisen directly about having committed a crime, the author criticizes the absolute prohibition of applying this type of arrest when criminal proceedings are initiated, as it is defined in the law of the Court of Cassation. Substantiating the fact that criminal proceedings have been initiated in itself does not exclude situations of immediate arrest of a person with external signs of a crime, the author considers the criterion of “no criminal proceedings have been initiated” to be unacceptable for considering an existence of reasonable suspicion that has arisen directly about having committed a crime, and instead puts forward the criterion of “the suspicion which is not arising from the evidence”. Referring to the other type of arrest, the author claims that the Criminal Procedural Code established a requirement to arrest the accused who is at large for taking him before the Court. Such a requirement is a manifestation of the presumption of deprivation of liberty, which contradicts the presumption of personal liberty and the international legal prohibition of arbitrary arrest. The author believes that the legislator considered the arrest of the accused mandatory for formal purposes, such as in order to consider the motion to detain the accused as proper and to initiate the detention proceedings, with the aim of sparing the court that arrested the latter from the burden of being considered a depriver of liberty.